FREQUENCY OF DISTURBANCE OF HORMONAL PROFILE (LH TO FSH RATIO) IN GIRLS OF AGE GROUP 14-18 YEARS WITH PRIMARY AMENORRHOEA - Mubashra Naz; Saadia khanum; Ammara Niaz (Journal of University Medical & Dental College, 1970)
ABSTRACT INTRODUCTION Objective: To determine the frequency of disturbance of hormonal profile (LH/FSH ratio) in girls of age group 14-18 years with primary amenorrhoea. Study Design: Descriptive cross sectional study Setting: Outpatient departments of obstetrics and gynecology departments of University Medical and Dental College and Punjab Medical & Dental College Faisalabad. Methods: Ninty five patients who met the inclusion criteria were selected for study through obstetrics and gynaecology outpatient departments. Exclusion criteria was strictly followed to limit the confounding variables. After detailed history and examination, serum LH and FSH levels were performed in all patients. According to results of investigations, disturbance of hormonal profile(LH/FSH ratio) was determined. Results: Out of 95 patients of age group 14-18 years with primary amenorrhoea, 6 (6.3%) were found to have disturbed LH to FSH ratio (Poly cystic ovarian Disease). Conclusion: It is important for health care providers to recognize that poly cystic ovarian disease can be a cause of primary amenorrhea, so that appropriate investigation and management strategies may be undertaken. The results of this study support screening for polycystic ovarian disease in pre menarchal and adolescent girls in an effort to improve the reproductive health of these girls.